Based Learning Model: Character Formation in Pancasila Learning for 5th Grade Students at UPTD SD Negeri 5 Makmur - Annisa, Dian; Suryana, Nana; Afiah, Nur; Nuriman; Mauliza, Rully; Zulaita (Yayasan Citra Dharma Cindekia, 2024)
This study aims to analyze the implementation of the Problem Based Learning (PBL) model in enhancing students' character in Pancasila learning for 5th grade students at UPTD SD Negeri 5 Makmur. The PBL model was chosen because this approach provides meaningful learning experiences through contexts that are relevant to students' lives, enabling them to understand and apply norms and rules in everyday life. This research uses a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation, which were then analyzed thematically to identify the impact of PBL on students' character development. The results show that PBL is effective in improving various aspects of students' character, such as responsibility, discipline, teamwork, and empathy. Students demonstrate more positive behavior at school and in their surroundings. Additionally, this model also enhances students' motivation to learn, as they are actively involved in the learning process. However, the implementation of PBL faces several challenges, such as the need for intensive guidance from teachers. To address these challenges, thorough planning and support from the school are necessary. In conclusion, the PBL model can make a significant contribution to students' character formation, especially in understanding and applying Pancasila learning. With further development, PBL can become an effective learning approach in elementary schools.